Yeast centrosomes act as organizing centers to promote Polo kinase–mediated adaptation to persistent DNA damage - Laurence Langlois-Lemay; Damien D’Amours (Proceedings of the National Academy of Sciences, 2025)
The ability of cells to overcome cell cycle arrest and adapt to the presence of unrepairable DNA damage is under the control of Polo-like kinases (PLKs) in eukaryotes. How DNA damage checkpoints are silenced or bypassed during the adaptation response is unknown, but the process requires enrichment of the Cdc5 PLK to microtubule organizing centers (MTOCs), such as the yeast centrosomes or spindle pole bodies (SPBs). Here, we found that SPBs play an active role as supramolecular organizing centers that coordinate Cdc5 recruitment and signaling to downstream effectors during the adaptation response to DNA damage. We show that SPB components Nud1, Spc110, and Spc72 are key effectors of Cdc5 recruitment to SPBs in the presence of sustained DNA damage. Following recruitment, Cdc5 transduces a phospho-signal to key structural subunits of the SPB, including Cnm67 and Mps3. We demonstrate these phosphorylation events are required to bypass cell cycle checkpoint arrest and enable effective adaptation to DNA damage. This response is specific because it cannot be recapitulated by a generic inactivation of MTOC activity. Collectively, our results indicate that centrosomes can act as supramolecular platforms to coordinate dynamic recruitment and substrate selection of PLKs during the DNA damage response (DDR).